TAMAN BACA CERIA SEBAGAI SUMBER LITERASI INFORMASI DIGITAL BAGI WARGA KELURAHAN BANDENGAN KOTA PEKALONGAN - Kustriyono, Erwan; Ayu Panuntun, Ida; Hayati, Rizka (Universitas PGRI Yogyakarta, 2023)
This Community Service activity aims to provide training and assistance solutions regarding the creation of library catalogs in the context of turning the Ceria Reading Park, Bandengan Subdistrict, Pekalongan City into a digital library. This activity also aims to make Community Service partners a source of information literacy in the digital era for the residents of Bandengan Subdistrict, Pekalongan City, especially visitors to Baca Ceria Park who consist of children and teenagers. The partners for this Community Service activity are the library staff at the Ceria Reading Park, Bandengan Village, Pekalongan City. The method for implementing Community Service activities is divided into 4 stages, namely socialization, training, mentoring and evaluation. The result of this Community Service activity is that in the early stages of socialization activities can be socialized well. In the training stage, Community Service partners can participate in training well and smoothly so that they can get the latest information and knowledge regarding how to create catalogs and digital literacy. Not only does the training end, the mentoring process can strengthen the knowledge and skills that have been obtained from the training as well as accompanying Community Service partners in the training. The final results of the evaluation stage showed that Community Service partners stated that their knowledge about cataloging and knowledge about digital literacy had increased and stated that this Community Service activity could provide benefits for Community Service partners. Keywords: Community Service, digital literacy, librarian, cheerful reading park